Concatenated convolutional codes with interleavers. - Benedetto, S. (IEEE Communications magazine)
This article presents a tutorial overview of the class of concatenated convolutional codes with interleavers, also known as turbo-like codes. They are powerful codes, formed by a number of encoders connected through interleavers, endowed by a decoding algorithm that splits the decoding burden into separate decoding of each individual code. Refinement of successive estimates of the information sequence is obtained by iterating the procedure of passing from one decoder to the other likelihood information decorrelated by the interleaver action. The key issues of code analysis and design are covered at the level of broad comprehension, without paying attention to analytical details.